FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MENGKONSUMSI TABLET ZAT BESI PADA IBU HAMIL DI PUSKESMAS BORONG KECAMATAN BORONG MANGGARAI TIMUR - Karundeng, Syela Elviani Stefani; Picauly, Intje; Toy, Sarci M. (Jurnal Pangan Gizi dan Kesehatan, 2023)
This research location is the Borong Health Center, East Borong Manggarai District, this study was carried out on August 21 – September 08, 2023. The type of research used is quantitative research by using cross sectional research building design. The population of all pregnant women with the number of 390 pregnant women scattered in 2 villages and 3 villages, namely Rana Loba Village, Ndora city Village, Nanga Labang Village, Compang Ndejing Village and Golo Kantar Village. Sampling technique uses simple random sampling with a sample of 56 pregnant mothers. Data obtained, analyzed using chi square with a level of disobedience p=0,05. The result of the research show that variables that are significantly related to the compliance of pregnant women in consuming iron tablets are education (0,000), attitude (0,000), family support (0,005) and health officer support (0,004). Variables that do not have significant relationships with the compliance of consuming iron tablets are ages (0,172), work (0,403) and knowledge (0,466). It is recommended that health workers need to provide more intense and effective communication to increase the awareness of pregnant women will benefit from consuming iron tablets.